(untitled) (Journal of the College of Basic Education, 2022)
Modern art education aims to provide learners with technical expertise and skills necessary for the development of emotional sense and elevating the level of aesthetic taste, as it has a special nature that emphasizes the role of art In the production of works of art and to provide them with technical and professional skills, and to introduce them to the basics and methods of teaching. in an in-depth manner. The art education teacher must possess the experience and expertise in order to be an educator aware of his responsibilities to In addition to his technical knowledge, and to transform his expertise and experience into a capacity for expression, to transform the material or raw material into a value.